2018
DOI: 10.3389/fnins.2018.00233
|View full text |Cite
|
Sign up to set email alerts
|

Left Parietal Functional Connectivity Mediates the Association Between COMT rs4633 and Verbal Intelligence in Healthy Adults

Abstract: In Chinese Han population, Catechol-O-methyltransferase gene (COMT) rs4633 is found to be associated with impaired cognitive process. We aimed to investigate the association between COMT rs4633 and verbal intelligence and the underlying neural mechanisms in Chinese Han healthy young adults. In 256 Chinese Han healthy young adults, we explored the modulatory effects of COMT rs4633 on verbal intelligence quotient (VIQ) and functional connectivity density (FCD) of the brain and the mediation effect of FCD on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The role of ZFPM2 has been associated with the whitematter pathways and processing speed (Giddaluru et al 2016). Functional connectivity of the left parietal cortex is known to mediate the association between COMT rs4633 and verbal intelligence (Xu et al 2018). Inter-regional genetic influences on cortical morphologies may underscore the inter-individual differences in structural and functional connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…The role of ZFPM2 has been associated with the whitematter pathways and processing speed (Giddaluru et al 2016). Functional connectivity of the left parietal cortex is known to mediate the association between COMT rs4633 and verbal intelligence (Xu et al 2018). Inter-regional genetic influences on cortical morphologies may underscore the inter-individual differences in structural and functional connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…One promising direction for exploring genetic associations is to investigate brain imaging phenotypes in relation to transcriptional profiles ( Romme et al, 2017 , Roshchupkin et al, 2016 , Ortiz-Terán et al, 2017 , Xu et al, 2018 ). Romme et al ( Romme et al, 2017 ) examined the role of genes in brain connectivity among schizophrenia patients and found that regional dysconnectivity was significantly correlated with the expression profile of schizophrenia risk genes across cortical regions, particularly those related to neuronal calcium signaling.…”
Section: Introductionmentioning
confidence: 99%